Laser-induced fluorescence of coumarin derivatives in aqueous solution: Photochemical aspects for single molecule detection - Eggeling, C; Brand, L; Seidel, C (1997)
The efficiency of detecting a single fluorescent coumarin dye molecule in aqueous solution by one-photon excitation (OPE) at 350 nm as well as by coherent two-photon excitation (TPE) at 700 nm is studied. The photostability, which is crucial for single molecule detection (SMD), is determined at a low irradiance for various coumarin derivatives using a 'cell-bleaching' method. The yields of photobleaching for these coumarins in aqueous solution are in the order of 10-3 to 10-4. Thus, most of the dyes are sufficiently stable to allow SMD. However, for SMD in a fluorescence microscope a high quasi-CW irradiance (at least 104 W cm-2) is necessary for efficient OPE by a pulsed, frequency doubled titanium:sapphire laser. Detailed investigations on the dye Coumarin-120 using fluorescence correlation spectroscopy (FCS), different repetition rates of the laser and transient absorption spectroscopy (TRABS) gave clear evidence that OPE at a high irradiance results in two-step photolysis via the first electronic excited singlet and triplet state, S1 and T1, producing dye radical ions and solvated electrons. Hence, this additional photobleaching pathway limits the applicable irradiance for OPE. Using coherent TPE for single molecule detection, saturation of the fluorescence was observed for a high quasi-CW irradiance (108 W cm-2), which may also be caused by photobleaching. Furthermore, TPE is deteriorated by other competing nonlinear processes (e.g. continuum generation in the solvent), which only occur above a threshold irradiance (7 x 107 W cm-2). Nevertheless, TPE allows an efficient detection of single Coumarin-120 molecules in water. Using a maximum likelihood estimator, we are also able to identify single dye molecules via their characteristic fluorescence lifetime of 4.8 ± 1.2 ns.